A relação entre estado e sociedade civil na implementação de políticas sociais e a fragilidade na efetivação do direito: Responsabilidade social empresarial na assistência à criança, adolescente e jovem na região metropolitana do Recife - Pintor, Katia Simone Alves (2015)
The present work analyses the relation between the State and the civil society in the social policy execution – since of each 1990 – in the neoliberal context of productive restricting and State reform. Has as goal investigate social business responsibility actions – SBR (RSE) – of assistance character, to children, teens and young. For this purpose, were observed four SBR\RSE experiences acting in Recife Metropolitan Region. That research it classifies how qualitative and uses documents for purpose the relation estabilished between RSE\SBR and social policies. It is based on Marxist theories and Gramscian and develops the conceptual debate\discussion about of State and civil society and the reconstruction of historical facts for the constituition social policies as the means of state-owned intervention in dealing for expressions of “social-issue”, of the social business responsibility and politics for child and teen.